PENGARUH KEDISIPLINAN DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN DENGAN MENGGUNAKAN METODE REWARD AND PUNISHMENT DI UPTD SDN 015931 PADANG MAHONDANG - Tonggi Marito Yesiska Tamba; Ribka Kariani Sembiring; Dyan Wulan Sari HS; Reflina Siinaga; Ester J. Simarmata; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of the influence of discipline and student learning outcomes in learning using the reward and punishment method in class III. This research is quantitative using descriptive methods. The research population was class III students at SDN 015931 Padang Mahondang, totaling 103 students. Samples were taken using Random Sampling techniques and were obtained from class III, totaling 30 students. The results of this research show that student learning outcomes are in the very good category with 80.1. The results of this research show that the correlation test shows that the correlation coefficient is rcount (0.938) ≥ rtable (0.361), so ha is accepted. So there is a very strong influence between discipline and student learning outcomes using the Reward and Punishment method in class III at SDN 015931 Padang Mahondang. It can also be seen from the t-test where tcount≥ ttable is 14.336 ≥ 2.042, thus stating that ha is accepted. This shows that there is a significant positive influence on the discipline and learning outcomes of students using the Reward and Punishment method in class III of SDN 015931 Padang Mahondang for the 2023/2024 academic year.